Evaluating liberal and hybrid approaches to peacebuilding : the case of Sierra Leone - Sitole, Sivuyile (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This thesis explores liberal and hybrid approaches to peacebuilding and their decisiveness in building sustainable peace in Sierra Leone. Contemporary peacebuilding interventions have been dominated by liberal peacebuilding, also known as liberal state-building. Post-conflict states have been transforming to replicate liberal states due to assumptions of liberal states being more peaceful and less likely to fall into conflict again than non-liberal states. There is growing criticism regarding the effectiveness of this approach as its initiatives have not always translated to sustainable peace. This failure is attributed to its minimal inclusion or exclusion of local actors in the peacebuilding process as well as its application of standardised approaches in complex contexts. In response to these shortfalls, international peacebuilding scholars propose an alternative approach that would combine the liberal and the local to produce a hybrid peace, which is inclusive and context-specific. This thesis tests the decisiveness of these approaches by examining the successful peacebuilding process in Sierra Leone. It then concludes that the peacebuilding interventions of Sierra Leone demonstrate how liberal peacebuilding initiatives have little or limited success when conducted without the inclusion of local actors. However, when local actors are included in the peace-building process to make meaningful contributions (hybrid peacebuilding), peacebuilding initiatives can have a much larger impact on society.
Keywords: Peace-building -- Sierra Leone; Sierra Leone -- Politics and government -- 1961-; Nation-building; Postwar reconstruction -- Sierra Leone